Bioinformatics with Python cookbook : learn how to use modern Python bioinformatics libraries and applications to do cutting-edge research in computational biology /: learn how to use modern Python bioinformatics libraries and applications to do cutting-edge research in computational biology. (2018) - Antao, Tiago
No abstract available